306. Rapid Detection Of Bloodstream Infections, Including Molecular Characterization, From Whole Blood. (31st December 2020) - Kadoom, Aram; Lockhart, Daniel; Kadoom, Yassar; Fauci, Sonia La; Rodgers, Andrew; Turner, James; Bennett, Helen; Jay, Paul; Thaker, Sumi; Mullen, William
Abstract: Background: Diagnosis of bloodstream infections (BSI) and treatment with appropriate antimicrobials is dependent upon fast and accurate information about the microorganism(s). The long time taken for a blood culture result, microbial identification and antimicrobial susceptibility testing (AST), can lead to poor antimicrobial stewardship. Many antimicrobial change decisions are based on the results of a Gram stain, with this being the first result available. Having results from a rapid test, direct from blood, which can confirm BSI and characterize the causative pathogen(s) would provide an improvement in antimicrobial stewardship and patient care. Methods: SepsiSTAT ® is a rapid molecular test, developed by Momentum Bioscience Ltd, for the detection of BSI, with a time-to-result of < 4 hours. It uses whole blood to detect viable microorganisms whilst also providing molecular characterization. Microorganisms are extracted from the sample using a proprietary process involving capture on magnetic microbeads. This is followed by Enzymatic Template Generation and Amplification (ETGA ® ) for ultra-sensitive, universal detection of viable bacterial and fungal species, based on detecting microbial DNA polymerase activity. Simultaneously, molecular characterization also provides genus/species identification. The detection limits of SepsiSTAT ® were evaluated for a broad panel of microorganisms, representing 80% of BSI reported to Public Health England (2018 report). Results: These results show a median detection limit (n=5) of < 10 cfu/mL in blood for microorganisms representing 77.4% of reported BSI, including key organisms such as E. coli, S. epidermidis and C. albicans . Notably, S. aureus, P. aeruginosa, E. faecalis, P. mirabilis and S. marcescens were all detected at < 1 cfu/mL. Conclusion: SepsiSTAT ® can detect microbes in low numbers, with a turnaround time substantially faster than traditional blood culture. Future development will aim to shorten time-to-results to < 3 hours, further benefiting patient outcomes and antimicrobial stewardship. Future studies in a clinical setting will seek to further demonstrate the efficacy and rapid turnaround time of the SepsiSTAT ® test. Disclosures: All Authors : No reported disclosures